Non-cognitive skills : the art of learning to learn well : data visualisation - Theh, Kang Ni (2016)
E-learning is a popular alternative tool for traditional classroom teaching but it lacks the face-to-face advantage. However, the limitation can be overcome with the use of automated tracking of user activities on the website, which the data can then be analysed to identify students’ behaviour and engagement on learning.